2015
DOI: 10.1016/j.jceh.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

HBsAg Level as Predictor of Liver Fibrosis in HBeAg Positive Patients With Chronic Hepatitis B Virus Infection

Abstract: Background and aims: Preliminary data suggests lower serum hepatitis B surface antigen level is associated with more severe liver fibrosis in HBeAg positive patients. We evaluated the association of HBsAg level with biochemical, virological, and histological features in asymptomatic patients with chronic HBV infection. Methods: HBsAg levels were measured at baseline in 481 asymptomatic, treatment naive patients with chronic HBV infection. Subjects were followed-up prospectively (median, 12; range, 8-36 months)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
2
18
0
2
Order By: Relevance
“…Both HBV DNA and HBsAg levels have a declining evolution as long as liver disease progress from the immune-tolerant status to the active hepatitis and cirrhosis in HBeAg-positive patients [41]. Although previous studies showed that HBV DNA level could predict the risk of cirrhosis and HCC, it has been proved a poor correlation between HBsAg level and HBV DNA across different phases of the chronic HBV infection [8,41].…”
Section: Predictor Of Liver Fibrosismentioning
confidence: 99%
See 4 more Smart Citations
“…Both HBV DNA and HBsAg levels have a declining evolution as long as liver disease progress from the immune-tolerant status to the active hepatitis and cirrhosis in HBeAg-positive patients [41]. Although previous studies showed that HBV DNA level could predict the risk of cirrhosis and HCC, it has been proved a poor correlation between HBsAg level and HBV DNA across different phases of the chronic HBV infection [8,41].…”
Section: Predictor Of Liver Fibrosismentioning
confidence: 99%
“…Although previous studies showed that HBV DNA level could predict the risk of cirrhosis and HCC, it has been proved a poor correlation between HBsAg level and HBV DNA across different phases of the chronic HBV infection [8,41]. Given that ALT measurement is a suboptimal marker for prediction of significant liver disease, it is recommended to have, as accurate as possible, an estimation of fibrosis and inflammation based on a reliable tool in order to decide antiviral treatment indication [42].…”
Section: Predictor Of Liver Fibrosismentioning
confidence: 99%
See 3 more Smart Citations